PURA LUHUR MUNCAKSARI DI BANJAR ANYAR DESA SANGKETAN KECAMATAN PENEBEL KABUPATEN TABANAN (KAJIAN EKOLOGI HINDU) - I Wayan Artayasa (Guna Widya: Jurnal Pendidikan Hindu, 2022)
Luhur Muncaksari temple is Khayangan Jagat temple in Tabanan Regency which was once believed to be a place to beg for rice safety, but later experienced a growing function as a place to beg for safety for all agricultural activities and the natural environment. Evidently, this temple is visited by many farming groups that develop various types of agricultural crops and environmentalist groups.This research explores Luhur Muncaksari temple based on the study of Hindu ecology. The data in this study was collected with observation techniques, interviews, documentation and literature studies. The results of this study show that, Hindu ecology at Luhur Muncaksari temple is contained in the aspect of theology (theo-ecology) shown by the belief in Ida Bhatara Pasedahan Agung (ruler of salvation, fertility, and yield), Tatangunan Sri Tumpuk (sacred aesthetics means ecological) and Paica Manik Galih (physical symbol of Bhatara Pasedahan Agung).Theo-ecological aspect has an effect on community ethics in designing various ideas, discourses, and environmental conservation actions both the temple environment and the natural environment in general.Ecological ethics that are built in society, constructing ecological education for the younger generation as a milestone in the consistency of natural sustainability.